PERAN KOMPETENSI KEPRIBADIAN GURU AL-QUR’AN HADIS DALAM MENINGKATKAN KEDISIPLINAN PESERTA DIDIK MA RADHIATUL ADAWIYAH MANGGA TIGA MAKASAR: The Role Of Qur'an And Hadith Teachers' Personal Competencies In Improving Student Discipline Ma Radhiatul Adawiyah Mangga Tiga Makassar - masnah, masnah; Juhasdi Susono; Muh. Natsir; Indri Karadona, Rosika (Piwulang: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the role of Al-Qur’an Hadith teachers’ personality competence in enhancing the discipline students at Madrasah Aliyah Radhiatul Adawiyah Mangga Tiga Makassar. The background of this research stems from the ongoing issue of students violating school rules and showing low levels of discipline, particularly in Al-Qur’an Hadith classes. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that teachers’ personality competence which includes traits such as honesty, responsibility, assertiveness, and integrityplays a significant role as a model in shaping students’ disciplinary character. Teachers with positive personality traits are able to create a conducive learning environment and motivate students to comply with school regulations. Furthermore, several supporting factors were identified, including a religious school environment, parental support, and collaboration between teachers and the school administration. The study concludes that teachers with strong personality competence can effectively foster student discipline, particularly in Al-Qur’an Hadith learning, and that this role is crucial to the overall success of the educational process.